MAXIMA card: is it advantageous to the New Straits Times Press (M) Berhad and its cardmembers ? Shahnaz Abdul Samad - Abdul Samad, Shahnaz (1992)
This project paper deals with the MAXIMA card, a discount card which is issued by the New Straits Times Press (Malaysia) Berhad. The card is meant for the readers of the New Straits Times Press and the New Sunday Times and it is advertised as a card which offers great advantages to the cardmembers.